THE IMPROVEMENT OF STUDENTS’ WRITING IN RECOUNT TEXT THROUGH T-CHART STRATEGY AT THE ELEVENTH GRADE STUDENTS OF SMAN I SUNGGUMINASA - Natsir, Ratu Yulianti (Elite : English and Literature Journal, 2017)
Abstract The objective of the research was to find out the improvement of the students achievement in writing ability through T-Chart strategy in term of content, organization, and language use. The researcher applied a pre experimental design with one group pre test and one group post test design. The subject of the research was the eleventh grade students of MAN 1 Sinjai Utara academic year 2015-2016. The sample consists of 26 students. The research was held in seventh meetings. The result of the data analysis showed that there was a significant difference between pre test and post test. The research findings indicated that T-Chart Strategy was effective to improve the students’ writing ability in terms of content, organization, and language use. It was proved by the students’ mean score in pre test was 32. 66 and post test was 73. 66. It showed that the students’ writing skill in post test was higher than pre test. The value of t-test from content, organization, and language use was 21. 36 and it was greater than t-table 2. 060 at the level of significant (p) = 0. 05 and degree of freedom (df) =26-1 = 25, it was found that the result of t-test value was greater than t-table (21. 36>2. 060). It is said that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui peningkatan prestasi belajar siswa dalam kemampuan menulis melalui strategi T-Chart dalam hal isi, organisasi, dan penggunaan bahasa. Peneliti menerapkan desain pra eksperimental dengan satu kelompok pre test dan satu kelompok post test design. Subjek penelitian adalah siswa kelas XI SMP MAN 1 Sinjai Utara tahun 2015-2016. Sampel terdiri dari 26 siswa. Penelitian dilakukan pada pertemuan ketujuh. Hasil analisis data menunjukkan bahwa ada perbedaan yang signifikan antara pre test dan post test. Temuan penelitian menunjukkan bahwa Strategi T-Chart efektif untuk meningkatkan kemampuan menulis siswa dalam hal isi, organisasi, dan penggunaan bahasa. Terbukti dengan nilai rata-rata siswa dalam pre test adalah 32. 66 dan post test adalah 73. 66. Hal ini menunjukkan bahwa kemampuan menulis siswa dalam post test lebih tinggi daripada tes awal. Nilai t-test dari isi, organisasi, dan penggunaan bahasa adalah 21. 36 dan lebih besar dari t tabel 2. 060 pada tingkat signifikan (p) = 0. 05 dan derajat kebebasan (df) = 26 -1 = 25, ditemukan bahwa hasil nilai t-test lebih besar dari t tabel (21. 36> 2. 060). Dikatakan bahwa hipotesis nol (H0) ditolak dan hipotesis alternatif (H1) diterima.